2005
DOI: 10.1161/circulationaha.105.520999
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Histological Substrate in Patients With Clinical Phenotype of Brugada Syndrome

Abstract: Background-The role of structural heart disease and sodium channel dysfunction in the induction of electrical instability in Brugada syndrome is still debated. Methods and Results-We studied 18 consecutive patients (15 males, 3 females; mean age 42.0Ϯ12.4 years) with clinical phenotype of Brugada syndrome and normal cardiac structure and function on noninvasive examinations. Clinical presentation was ventricular fibrillation in 7 patients, sustained polymorphic ventricular tachycardia in 7, and syncope in 4. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
224
5
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(253 citation statements)
references
References 28 publications
17
224
5
7
Order By: Relevance
“…Some microscopic myocardial alterations have been reported, suggesting that the channelopathy may induce cardiomyopathic changes in some patients. 11,12 Thus, the presence of important structural alterations should suggest an alternative diagnosis.…”
Section: Clinical Diagnosis Diagnostic Criteriamentioning
confidence: 99%
“…Some microscopic myocardial alterations have been reported, suggesting that the channelopathy may induce cardiomyopathic changes in some patients. 11,12 Thus, the presence of important structural alterations should suggest an alternative diagnosis.…”
Section: Clinical Diagnosis Diagnostic Criteriamentioning
confidence: 99%
“…27) Frustaci, et al and our colleagues Ohkubo, et al documented structural abnormalities, including right ventricular myocarditis, right ventricular cardiomyopathy, and cardiomyopathic changes in endomyocardial biopsy samples. 16,18) Furthermore, Coronel, et al described histopathologic features of a heart explanted from a Brugada syndrome patient, and showed that right ventricular hypertrophy and fibrosis with epicardial fatty infiltration as well as conduction slowing were based on interstitial fibrosis, not transmural repolarization differences, and that these features caused the ECG signs and explained the VF. 7) Recent work in the same laboratory confirmed that local depolarization abnormalities are the dominant pathophysiologic mechanism for the type 1 Brugada electrogram.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] Furthermore, structural abnormalities in the right ventricle are reported in Brugada syndrome. [16][17][18] We conducted a single-center case-control electroanatomic mapping study in patients with and without Brugada syndrome to identify the arrhythmogenic substrates in Brugada syndrome.…”
mentioning
confidence: 99%
“…In some aspects, this phenotype resembles PCCD, although in the later fibrosis was found to be limited to the conduction system area (Lenègre and Moreau, 1963;Lev, 1964). However, it is worth noting that fibrosis has also been observed in patients with the Brugada syndrome (Coronel et al, 2005;Frustaci et al, 2005). More recently, it was shown that Scn5a ± mice display variable degrees of conduction defects when young (10 weeks old): some mice have only mild prolongation of the QRS interval while others have more severe QRS prolongation associated with RR or SS patterns (Leoni et al, 2010).…”
Section: A Model For the Brugada Syndrome And Conduction Disorders: Tmentioning
confidence: 97%